Computational Modelling and Optimization of a Methylammonium‐free Perovskite and Ga‐free Chalcogenide Tandem Solar Cell with an Efficiency above 25 %. Issue 32 (22nd August 2022) - Kumar, Anjan; Singh, Sangeeta; Pandey, Rahul
Abstract: Multi‐junction solar cells connecting two or more cells with significantly different bandgaps have a lot of promise for exceeding the Shockley Queisser (S‐Q) efficiency limit of single‐junction‐based photovoltaic devices. In this article, a new class of tandem devices has been proposed and investigated for improved efficiencies. The proposed tandem cell is connected in monolithic two‐terminal tandem configurations with wide bandgap formamidinium (FA) based perovskite absorber (FA0.85 Cs0.15 Pb (I0.85 Br0.15 ) 3 ) (1.6 eV) (Cs15/Br15)) on the top cell and low bandgap gallium free chalcogenide (CuInSe2) absorber on the bottom cell. Doped FA‐based perovskite material is preferred over commonly used FAPbI3 as it is a proven fact that adding modest quantities of cesium and bromine stabilizes the optically active black phase of FAPbI3 Perovskite and increases overall device performance. In contrast, bottom CuInSe2 (CIS) absorber material is selected considering its good thermal stability and excellent light‐absorbing capabilities in a broad‐spectrum range. The feasibility of the suggested tandem configuration is assessed in two steps. First, a 1.6 eV perovskite top cell is simulated and calibrated to suit the state‐of‐the‐art power conversion efficiency of 17.5 %, followed by a 1.04 eV CuInSe2 ‐based bottom cell with a calibrated efficiency of 16.2 %. Both devices are tested for tandem configuration once the standalone (top and bottom) subcells have been calibrated. At varied absorber thicknesses in both the top and bottom subcells, the current matching conditions are achieved. At optimal thicknesses of 700 nm and 590 nm for the bottom and top absorbers, respectively, the overall tandem structure obtained an excellent power conversion efficiency of 25.13 %. Results reported in this study may pave the way for the development of high‐efficiency perovskite/CIS based tandem solar cells in the future. Abstract : Computational modelling of two terminal‐based monolithic perovskite/CIS tandem solar cells with a decent power conversion efficiency of 25.13 % is reported. The top cell is illuminated with standard AM 1.5G solar spectrum, whereas the bottom cell is illuminated with filtered spectrum transmitted from the top cell. The current matching conditions between the top and bottom subcell are obtained by varying the thicknesses of absorber layers in both the top and bottom subcell. A Tandem J‐V curve is constructed at the different current matching points, and solar parameters are calculated.